Pamięć przeszłości versus Historia. O Lodzie Jacka Dukaja - Gorliński-Kucik, Piotr (Tematy i Konteksty, 2015)
There are at least two equivalent interpretations of Jacek Dukaj’s 'Lód'. It may be interpreted as a novel about the continual progress of homo sapiens, and therefore – similarly to the majority of the writer’s works – from the viewpoint of transhumanism; as well as – and this is what the paper is dealing with – as ‘a treatise on the freedom from Idea’. Dukaj’s alternative story has been created on the basis of modification of the laws of our physics (an unknown element from outer space falls to the ground) and an intellectual play with the Lwów-Warsaw school findings. As a result, the literary world of 'Lód' has been divided into the spheres of the influence of Summer and Winter which are – according to this interpretation – the metaphor of relativism and essentialism. In turn, the analysis of the selected excerpts proves that the novel is also about the narrative character of history. The last part of the paper is – in the intention of the author – a tentative attempt to present certain possibilities for making use of this metaphor in the context of literary studies, in terms of writing the history of literature.